2020
DOI: 10.7717/peerj.9266
|View full text |Cite
|
Sign up to set email alerts
|

Legacy effects of historical grazing alter leaf stomatal characteristics in progeny plants

Abstract: Grazing, one of the primary utilization modes of grassland, is the main cause of grassland degradation. Historical overgrazing results in dwarf phenotype and decreased photosynthesis of perennial plants. However, it remains unknown what the mechanism underlying of this legacy effect is, and the role of stomata in the resulting decreased photosynthesis also remains unclear. To address these questions, differences in stomatal density, length and width on both adaxial and abaxial epidermis were compared between o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 80 publications
(60 reference statements)
0
8
0
Order By: Relevance
“…In addition, ABA regulates the stomatal aperture by changing the volume of guard cells that control gas exchange (Chen et al, 2021 ). Our previous study found that stomatal conductance of overgrazed L. chinensis significantly decreased (Yin et al, 2020 ), which may be related to ABA content changes.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, ABA regulates the stomatal aperture by changing the volume of guard cells that control gas exchange (Chen et al, 2021 ). Our previous study found that stomatal conductance of overgrazed L. chinensis significantly decreased (Yin et al, 2020 ), which may be related to ABA content changes.…”
Section: Discussionmentioning
confidence: 92%
“…In this study, there was an increase in the expression level under red + drought conditions, especially in the drought‐sensitive cultivar Agria; however, a similar response was not observed in the tolerant cultivar Sante. There are studies available in the literature on cyclin‐P3‐1, and its function is described by stomatal development and activity, as reported in Leymus chinensis (Yin et al, 2020 ). This could suggest the role of cyclin‐P3‐1 and StGATA3 in the drought response in potato, as positive transcriptional induction of each seems to stimulate the response both for sensitive and tolerant cultivars; however, the increase in expression was higher in sensitive cultivar because it experienced severe drought.…”
Section: Discussionmentioning
confidence: 99%
“…In northern China, desert steppe is the most arid grassland type (Perrings & Walker 1997), where the environment is severe and heavily impacted by large climate uctuations (Ren et al 2018). Over the previous two decades, desert steppe also experienced major changes in vegetation structure as intense livestock ranching operations arose (Yin et al 2020). Previous research in the desert steppe of northern China found clear evidence for impacts of intensive grazing on community composition, individual species traits such as plant height, leaf area, speci c leaf area, seed mass, and stoichiometry of organisms (Jiangwen 2018;Ye et al 2020), and ecosystem functions such as productivity, plant diversity, and photosynthetic capacity (Wang et al 2011;YuXi.…”
Section: Introductionmentioning
confidence: 99%